2017
DOI: 10.1111/cxo.12518
|View full text |Cite
|
Sign up to set email alerts
|

Care solution effects on contact lens in vivo wettability

Abstract: This novel thin film interferometric technique was able to measure, objectively, contact lens in vivo wettability, following the use of care solutions. COMPLETE was the only solution that showed no significant change in the lens wettability (with the all parameters) between the initial and the end of day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…of the CL performance [1,14,28]. The data on the impact of internal wetting agents on the contact angles of worn SiHy CLs are also inconclusive [7,8] and although it was found that the presence of PVP (wetting agent) does not significantly improve the clinical performance of SiHy [31], the small sample size (40 patients per CL sample) limited the statistical power of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of the CL performance [1,14,28]. The data on the impact of internal wetting agents on the contact angles of worn SiHy CLs are also inconclusive [7,8] and although it was found that the presence of PVP (wetting agent) does not significantly improve the clinical performance of SiHy [31], the small sample size (40 patients per CL sample) limited the statistical power of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Great efforts have been devoted to the design of daily disposable SiHy CLs that can maintain high wettability even after extended wear. Different approaches have been implemented [7,8]: (i) from incorporation of wetting agents (polyvinylpyrrolidone, poloxamers, etc.) in the CL core and in CL solutions to (ii) the design of sophisticated CL surfaces with high water holding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Indirectly, contact lens wettability can be evaluated by assessing features of the PLTF that provide useful information about the level of tears spreading on the lens. Tear coverage can be assessed by examining any PLTF deficiency on the contact lens surface through slit lamp observation by examining the quality of a specular reflection at high magnification, using interferometry observation techniques and with the use of grading scales [92,[95][96][97][98][99][100][101][102][103]. Another possibility is to evaluate the optical quality of the contact lens on the eye in terms of higher-order aberrations, since the surface wetting of a contact lens influences optical quality [104].…”
Section: Measuring Wettability In Vivomentioning
confidence: 99%
“…its location being predominantly on the surface or in the bulk of the lens) were partially dependant on whether a surface coating on the lens was present [253]. While several studies report differences in lens wettability or adsorption of wetting agents with different lens care solutions in vitro [254,255], reports are inconsistent on the ability of lens care solutions to maintain contact lens wettability during wear [103,106,110,[256][257][258].…”
Section: Lens Care Solutionsmentioning
confidence: 99%
“…Tear film dysfunction causes pain and enhanced immune activity, which may interfere with vision [18]. Some studies have shown that the coefficient of friction (COF) of silicone hydrogels may be changed due to long-term reaction with the tear film components, indicating that long-lasting moist lens is favourable for maintaining a low COF in a long time [19], and some research studies related to the design of novel highly weTable contact lens materials have been done already [20][21][22]. Blinking and eye rotation are the most important physiological processes for lens and lens friction, which can lead to various corneal infections, corneal ulcers, decreased vision, and other symptoms [23].…”
Section: Introductionmentioning
confidence: 99%